"Sibaaqun" Edukasi Pengenalan Huruf Hijaiyah Melalui Permainan Papan - Moch. Tryandi Budiman Sasmita; Samuel Gandang Gunanto; Pandan Pareanom Purwachandra (Journal of Animation and Games Studies, 2019)
The world of children is identical with a games or playing. Children learn by playing or by playing a game. But as time goes on, many games have more negative effects on children. The creation of works with the title "Sibaaqun Educational Media Introduction to Hijaiyah Letters and Islamic Literature through the Board Game", has the purpose of conveying knowledge of Islam and introducing the Hijaiyah letters to children through board games. The creation of the work of this board game intends to reduce the negative impact that children receive when playing. By making a game by inserting education in it, and also how to make the game run is non-boring. With the creation of this work, children can learn by playing. Children will get Islamic education in a board game.Keywords: board game, Hijaiyah letters, Islamic games, children's games